'It's need, not greed': needs and values at work in an Italian social cooperative - Foley, R (2018)
Among the key issues that arise in research of cooperatives are their supposedly hybrid nature and how they are able to balance both social and economic goals. I contend that the concept of ‘needs’ has become an important differentiating factor for the cooperatives I studied in Emilia Romagna. Placing this concept centrally in an analysis of cooperative practice helps to reveal the interplay between various value systems, reaching beyond arguments of the degeneration of cooperatives or the reproduction of dominant models, which both assume a one-way flow of influence. The recent history of the cooperative movement in Italy shows that these institutions have developed along with changing conceptions of need, supported by broader social movements and value systems. The cooperative network is today of central importance, and seen as an egalitarian means to share ideals and drive local innovation. However, my research shows that the instrumentalisation of the concept of ‘need’ also naturalises certain aspects of capitalist practice and has consequences for the enactment of other values within the cooperative. For example, in one cooperative I examined, the focus on meeting the members’ needs for work was important in justifying a decision to merge with another cooperative despite a decision-making process that was seen as less than entirely democratic. This orientation also justified the use of precarious labour, and the need to protect members’ livelihoods helped to justify low pay for internships and municipal job placements, as opposed to furthering the cooperative values of equity and equality. While the cooperative workers desired an element of personal relations, this was sometimes seen to be at odds with the focus on production and the maintenance of jobs. The marketing of more ethical products with reference to their social added value highlighted the central role of individual consumer citizens in bringing about change, which also reinforced divisions within the cooperatives based on who was more or less able to make these choices. In conclusion, I argue that while ‘needs’, like ‘added value’, can unite social and economic concepts of value, this also naturalises certain aspects of capitalist practice, particularly in this case where employment emerges as the primary need to be met. This leads me to suggest that the focus on meeting needs, as opposed to focusing on achieving specific ideals such as democracy and equality, may not be as effective to create alternative practice.